Nonlinear mixed convection couple stress tri-hybrid nanofluids flow in a Darcy-Forchheimer porous medium over a nonlinear stretching surface - Gul, Taza; Saeed, Anwar (Waves in random and complex media, 2025)
This work addresses the improvement of thermal flow for couple stress Darcy-Forchheimer ternary hybrid nanofluid flow past a nonlinear stretching surface. Three different types of nanoparticles, namely $ Ti{O_2},CoF{e_2}{O_4},MgO $ Ti O 2 , CoF e 2 O 4 , MgO , have been spread into the base fluid considered as water. The new combination $ (Ti{O_2} + CoF{e_2}{O_4} + MgO/{H_2}O) $ ( Ti O 2 + CoF e 2 O 4 + MgO / H 2 O ) has been observed for thermal characteristics with the influence of nonlinear convection and thermal radiations subject to the porous surface. The system of equations that administered the flow and energy equations has been altered to dimension-free category by implementing a set of appropriate variables. It has been noticed that velocity profiles decline with augmentation in volumetric fractions of nanoparticles, nonlinearity index of sheet and porosity parameter whereas it upsurges with Grashof and nonlinear Grashof numbers. Temperature profiles upsurge with growth in thermal ratio, thermal radiation factors and volumetric fractions of nanoparticles. Growth in radiation parameter and Brinkman numbers supports entropy rate and opposes Bejan number.